Faktor-Faktor yang Mempengaruhi Kualitas Dokumentasi Keperawatan: A Systematic Review - Sholihin Sholihin; Tintin Sukartini; Aria Aulia Nastiti (FORIKES, 2020)
Background: Nursing documentation is the most important part of the nursing profession, providing structured, consistent and effective communication to give quality services to patients based on professional and legal standards. Objective: To identify scientific evidence about the factors that influence the quality of nursing documentation. Methods: This systematic review was compiled based on study of literature from various journal data bases in the last 5 years, including Scopus, Sciencedirect, Proquest, and Google Scolar by conducting a comprehensive review using the PRISMA guidelines. Keywords used were